Influence of agro-ecological service crop termination and synthetic biodegradable film covering on Aphis gossypii Glover (Rhynchota: Aphididae) infestation and natural enemy dynamics. Issue 4 (11th April 2017) - Magagnoli, Serena; Depalo, Laura; Masetti, Antonio; Campanelli, Gabriele; Canali, Stefano; Leteo, Fabrizio; Burgio, Giovanni
Abstract: Agro-ecological service crops (ASC) can increase the vegetation complexity of agroecosystems leading to a positive impact on natural enemies of arthropod pests and on weed control. In this study, two ASC terminations (green manure and roller crimper) and a Mater-Bi-mulched control (MB) were compared in order to describe the effects on pests and beneficial dynamics in an organic vegetable system. The trials were conducted over two consecutive growing seasons in 2014 and 2015. Zucchini were grown as cash crop and barley as ASC. Pests and natural enemies were monitored fortnightly by visual samplings along the whole zucchini-growing season. Zucchini plants showed a faster vegetative growth in MB treatment than in ASC terminations. In both years, MB plots were characterized by higher soil temperature and higher leaf nitrogen concentration resulting in plants more susceptible to Aphis gossypii infestations. In all the experimental plots, natural enemies controlled aphid infestations and no insecticide and sprays were necessary. In conclusion, the tested ASC techniques have been suggested as a tool to mitigate aphid infestation.